KAJIAN KONDUKTIVITAS HIDROLIK TANAH GAMBUT PADA BERBAGAI TINGGI MUKA AIR TANAH DI DESA CATUR RAHAYU KECAMATAN DENDANG PROVINSI JAMBI - Ilmi, Rozatul; Junedi, Heri; Mastur, Agus Kurniawan (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Conversion of forests to oil palm and areca nut plantations contributes to the decline in groundwater levels, which ultimately causes drought. Differences in groundwater levels also affect the physical characteristics of peat, including its hydraulic conductivity. This study aims to analyze hydraulic conductivity values ​​at various depths of shallow (<40 cm) and deep (>40 cm) groundwater levels. This study was conducted for three months in the peatlands of Catur Rahayu Village, Dendang District, East Tanjung Jabung Regency, Jambi Province, covering the preparation to post-research stages. This study was conducted using a purposive sampling method, observations based on sample selection criteria including: (1) distance from the canal (50 m and 100 m), (2) variations in peat maturity levels (fibric, hemic, sapric), and (3) GWL depth (<40 cm vs. >40 cm). Hydraulic conductivity measurements were carried out three times per point to minimize errors, with instrument calibration before data collection. The results of the study showed that the hydraulic conductivity value at shallow groundwater levels ranged from 3.80 - 29.50 m / day, higher than the conductivity at deep groundwater levels which ranged from 3.38 - 4.14 m / day indicating the need for GWL regulation to mitigate peat drought. Based on the results of the study, other factors that influence hydraulic conductivity are peat characteristics, especially its maturity level. The more mature the peat, the smaller the pore size due to shrinkage of organic matter particles and decreased organic matter content; therefore, the hydraulic conductivity rate becomes slower. This study also revealed that the more mature the peat, the higher its volume weight, which has an impact on reducing hydraulic conductivity. This is due to the smaller size of organic matter particles, which reduces the pore space in the soil and increases its density. As a result, the movement of water in the soil becomes slower, which causes a decrease in the hydraulic conductivity value.